A guide to health and safety prosecutions - Appleby, Michael (Thomas Telford, 2007)
Written against the backdrop of increasing fines for health and safety offences against companies and individuals, this practical guide provides directors and managers with straightforward and practical advice on relevant issues.
Keywords: Industrial safety -- Law and legislation -- Great Britain.; Industrial hygiene -- Law and legislation -- Great Britain.; elektronické knihy; electronic books